"I heard about the way the animals are treated and slaughtered, and I don't like it"—Attitudes of vegetarians or vegans who have learning disabilities. (17th September 2020) - Bates, Claire
Accessible summary: People with learning disabilities who are vegetarian or vegan in this study choose not to eat meat because of their love of animals, the concern for their welfare and a dislike of them being killed to eat. People with learning disabilities in this study did not think other people with learning disabilities are aware that animals are killed for meat and do not have the information to make an informed choice about eating meat. Participants in this study have supportive staff and families who help them to cook and eat a vegetarian or vegan diet. Some people with learning disabilities worry about the healthiness and fat content of meat, and also diseases that animals may have which go into meat. Abstract: Background: Adopting a vegetarian diet is becoming increasingly popular within the UK, for reasons such as perceived health benefits and concerns over animal welfare. The study explores attitudes towards vegetarianism/veganism among adults with learning disabilities. Materials and Methods: Semi‐structured interviews were conducted with eight people with learning disabilities who did not eat meat across the UK. Results: Participants who adopted a meat‐free diet did so predominantly for animal welfare. Participants cared passionately about the welfare of animals but were reluctant to advocate their lifestyle to other people with learning disabilities, where they are in the minority for their dietary choices. Participants felt most people with learning disabilities were not made aware of the reality that animals are killed for food and that they should have accessible information to make an informed choice about whether to eat meat. Conclusions: Holding the identity as a vegetarian could potentially facilitate integration into mainstream organisations where people hold similar ethical beliefs; however, this is unlikely unless organisations increase their inclusivity such as providing accessible information.